SAT0291 THE ROLE OF X-LINKED INHIBITOR OF APOPTOSIS PROTEIN (XIAP) IN SYSTEMIC SCLEROSIS. (2nd June 2020) - Bergmann, C.; Hallenberger, L.; Merlevede, B.; Dees, C.; Chen, C. W.; Distler, O.; Schett, G.; Distler, J.
Abstract : Background: Pathologic activation of fibroblasts is a central feature of fibrotic tissue disease in Systemic Sclerosis (SSc). Although individual key signaling pathways of fibroblast activation such as transforming growth factor β (TGFβ) and WNT/β-catenin signaling have been identified, the consequences of the concomitant upregulation of these pathways and their crosstalk are incompletely characterized. Given the high medical need, the identification of mutual activation and amplification loops of profibrotic signals is essential to identify novel candidates for antifibrotic therapies. XIAP (X-linked inhibitor of apoptosis protein) is a ubiquitously expressed member of the IAP protein family which are implicated in the regulation of various cellular functions and tissue turnover. XIAP was recently described to be implicated in WNT/β-catenin signaling and TGFβ signaling. Objectives: The aim of this study is to characterize the role of XIAP in fibrotic disease. Methods: XIAP-expression was analyzed by qPCR, IF and Western blot. XIAP was targeted pharmacologically and with siRNA. The activation of WNT/β-catenin signaling was assessed by analyses of WNT target genes, by TOPflash/FOPflash luciferase reporter assay and in reporter mice. In vivo, XIAP inhibition was analysed in two different models of fibrosis. Results: The expression of XIAP is increased in the skin of SSc patients compared to matched healthy individuals with a particular prominent expression in fibroblasts. The overexpression of XIAP is more pronounced in SSc patients with diffuse and active skin fibrosis compared to SSc patients with limited and inactive disease. The overexpression of XIAP is also reflected in several experimental fibrosis models: the model of sclerodermatous graft versus host disease, the model of bleomycin induced skin fibrosis and Topoisomerase I induced fibrosis (TopoI) mice. TGFβ induces the expression of XIAP in vitro and in vivo and treatment with the TGFβ1 receptor antagonist SD208 reverses the TGFβ induced expression of XIAP. Inhibition of XIAP with embelin or siRNA reduces the TGFβ induced activation of fibroblasts with reduced collagen release and reduced expression of myofibroblast markers. In addition, XIAP inhibition reverted the activated fibroblast phenotype in SSc fibroblasts with reduced expression of stress fibers and αSMA. The antifibrotic effects of XIAP inhibition occurred in non-toxic doses as demonstrated by MTT and by TUNEL staining. In vivo, inhibition of XIAP reduced skin fibrosis in the models of bleomycin induced skin fibrosis and in TopoI-induced skin and lung fibrosis as demonstrated by analysis of dermal thickening, dermal hydroxyproline content and by analysis of myofibroblast differentiation. Mechanistically, XIAP inhibition reduced the activation of WNT/β-catenin signaling as demonstrated by TOPflash reporter assays and by the analysis of WNT target genes. Conclusion: XIAP is upregulated in SSc fibroblasts and murine SSc models in a TGFβ-dependent manner and promotes fibroblast activation by fostering canonical WNT signaling. Our data suggest that XIAP mediates an amplification loop between TGFβ and WNT/β-catenin signaling. Inhibition of XIAP may thus be a novel approach to target aberrant WNT/β-catenin signaling in fibrotic diseases. Disclosure of Interests: Christina Bergmann: None declared, Ludwig Hallenberger: None declared, Benita Merlevede: None declared, Clara Dees: None declared, Chih-Wei Chen: None declared, Oliver Distler Grant/research support from: Grants/Research support from Actelion, Bayer, Boehringer Ingelheim, Competitive Drug Development International Ltd. and Mitsubishi Tanabe; he also holds the issued Patent on mir-29 for the treatment of systemic sclerosis (US8247389, EP2331143)., Consultant of: Consultancy fees from Actelion, Acceleron Pharma, AnaMar, Bayer, Baecon Discovery, Blade Therapeutics, Boehringer, CSL Behring, Catenion, ChemomAb, Curzion Pharmaceuticals, Ergonex, Galapagos NV, GSK, Glenmark Pharmaceuticals, Inventiva, Italfarmaco, iQvia, medac, Medscape, Mitsubishi Tanabe Pharma, MSD, Roche, Sanofi and UCB, Speakers bureau: Speaker fees from Actelion, Bayer, Boehringer Ingelheim, Medscape, Pfizer and Roche, Georg Schett Speakers bureau: AbbVie, BMS, Celgene, Janssen, Eli Lilly, Novartis, Roche and UCB, Jörg Distler Grant/research support from: Boehringer Ingelheim, Consultant of: Boehringer Ingelheim, Paid instructor for: Boehringer Ingelheim, Speakers bureau: Boehringer Ingelheim